Eco-Santri: Pelatihan Menanam Sayur dengan Limbah Cangkang Telur untuk Membangun Karakter Cinta Lingkungan di TPQ Sabilil Mustaqim - Bayu Ardiwansyah; Iswati Iswati; Heri Cahyono; Kuliyatun Kuliyatun; Prabowo Adi W; Cahaya Khaeroni; Nindita Putri; Ahmad Fitra Sumbono; Restu Syifa Nida (Asosiasi Periset Bahasa Sastra Indonesia, 2025)
This community service program aims to foster environmental awareness in students by training them to grow vegetables using egg shell waste. The activity was carried out at TPQ Sabilil Mustaqim, Metro City, as a response to the low ecological awareness among children and the underutilization of household organic waste. The method used includes initial observation, education based on Islamic values, and hands-on practice of planting vegetables using egg shells as media. The results show an improvement in students' understanding of the importance of environmental conservation, a positive attitude change such as avoiding littering, and the formation of a “Santri Planting Corner” as a sustainable ecological learning space. Additionally, this program successfully integrates Islamic values with environmental literacy through a simple yet effective practical approach. This approach not only builds ecological awareness in children from an early age but also offers a model that can be replicated in other religious educational institutions. The training has proven effective in connecting character education, environmental conservation, and community empowerment based on TPQ, contributing to the creation of a generation that is both environmentally conscious and morally upright.